2020
DOI: 10.1042/bsr20192465
|View full text |Cite
|
Sign up to set email alerts
|

ERRα activates SHMT2 transcription to enhance the resistance of breast cancer to lapatinib via modulating the mitochondrial metabolic adaption

Abstract: Lapatinib, a tyrosine kinase inhibitor, can initially benefit the patients with breast tumors but fails in later treatment due to the inevitable development of drug resistance. Estrogen-related receptor α (ERRα) modulates the metabolic adaptations in lapatinib-resistant cancer cells; however, the underlying mechanism remains unclear. ERRα was predicted to bind to the serine hydroxymethyltransferase 2 (SHMT2) transcription initiation site in the ER- and HER2-positive cell line BT-474; thus, we hypothesize that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…Moreover, SHMT2 has been found to be associated with a poor prognosis in hepatocellular carcinoma (Ji et al, 2019), intrahepatic cholangiocarcinoma (Ning et al, 2018), breast cancer (Bernhardt et al, 2017) and gastrointestinal tumors (Liu et al, 2019). In addition, ERRα can activate SHMT2 transcription by targeting its promoter region to enhance breast cancer resistance to lapatinib (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SHMT2 has been found to be associated with a poor prognosis in hepatocellular carcinoma (Ji et al, 2019), intrahepatic cholangiocarcinoma (Ning et al, 2018), breast cancer (Bernhardt et al, 2017) and gastrointestinal tumors (Liu et al, 2019). In addition, ERRα can activate SHMT2 transcription by targeting its promoter region to enhance breast cancer resistance to lapatinib (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ERRα in drug resistance has been widely studied in breast cancer and osteosarcoma (44)(45)(46)(47)(48). However, its role in PCa drug resistance was rarely examined.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ERRα and PGC-1α regulate the expression of genes involved in the folate cycle (Audet-Walsh et al, 2016) and the methionine cycle (Vernier et al, 2020a). Furthermore, ERRα, ERRγ, and PGC-1α regulate the enzymes involved in glutamine metabolism in HER2-positive breast cancer cells (McGuirk et al, 2013;Deblois et al, 2016;Vernier et al, 2020b), which is implicated in resistance to the HER2 inhibitor lapatinib (Li et al, 2020;Vernier et al, 2020b). A recent study showed that ERRα and ERRγ modulate ROS homeostasis, and that ERRγ is associated with resistance to paclitaxel, an anticancer drug that induces ROS.…”
Section: Err/pgc-1-mediated Metabolic Reprogramming In Breast Cancermentioning
confidence: 99%